A superfluid universe - Huang, Kerson (2016)
"This interesting book provides the physical and mathematical background for a theory describing the universe as a quantum superfluid, and how dark energy and dark matter arise. Presenting a novel theory spanning many different fields in physics, the key concepts in each field are introduced. The reader is only expected to know the rudiments of condensed matter physics, quantum field theory and general relativity to explore this fascinating new model of dark matter and dark energy as facets of a cosmic superfluid. Readership: Students, researchers, and all readers interested in cosmology"--
Keywords: Superfluidity; Matter -- Properties; Quantum theory